Comparative study of fragrance compound from Mangifera Indica.L by different method extraction / Nazrin Syam Amirul and Dr Norhusna Mohamad Nor - Amirul, Nazrin Syam; Mohamad Nor, Norhusna (2022)
Mangifera Indica.L known as mangos where the genus and the family have been categorized as an Anacardiaceae. The genus Mangifera has contained several species that have edible fruit and the lower quality fruit is commonly known as wild mangos Mangifera India.L that has consisted chemical constituent include aliphatic compounds, terpenoids, flavonoids, alkaloids, coumarins, terpenoids saponins, polyphenolics, tannins, and essential oils. Mangifera Indica.L has fragrance compound or aromatic compound which it consists in more than 270 volatile compound that can be found where the sesquiterpenes and monoterpenes most abudance in these mangos. Monoterpenes compound consist limonene, β-pinene, δ-3-carene, α-phellandrene, β-myrcene, α- terpinene, α-terpinolene, β-phellandrene, (E)-β-ocimen and terpinene while sesquiterpenes consist β-caryophyllene, α-gurjunene, α-copaene, α-and caryophyllene. Three method of extraction of volatile compound would be compared such as simultaneous distillation, solid phase micro extraction and solvent extraction. These all compound have been detected and analyse using GC-MS where the fragrance compound of Mangifera Indica is identify. Simultaneous distillation–extraction (SDE) from three previous study which is total 29 compounds has been identify.The class of compound has been found were monoterpene, sesquiterpene, alcohol, aldehyde, acids and alkene. Solvent extraction have been found 19 volatile compounds of mango while Solid Phase Micro-extraction. (SPME) from previous study 21 compounds have been identify. The similarity of volatile compound identified in the threemethod extraction only monoterpene such as beta phellandrene, beta myrcene, alpha thujene, δ- 3-Caren, alpha-terpinene, limonene and terpinolene. The high yield extraction of Mangifera Indica.L determine using formulate after extraction from previous study. Solid phase Micro extraction has high yield extraction of volatile compound.